Investigation the Effect of Increasing Board Density and Amount of UF Resin on Particleboard Properties - Farnaz Eslah; A.Akbar Enayati; Mehdi Faezipour; Mehdi Tajvidi (Iranian Journal of Wood and Paper Industries, 2012)
In order to investigation the effect of increasing board density and amount of UF resin on particleboard properties, this study was carried out. .Regarding two variable parameters: board density at three level (520, 620 and 720Kg/m3) and percentage of UF resin (6, 7, and 8%),one layer particleboards with16mm nominal thickness were manufactured. Physical and mechanical properties such as MOR, MOE, IB and thickness swelling (after 24 hours immersion in water) were measured. The results showed that with increase in board density from 520 to 720 Kg/m3, MOR and MOE were increased and dimensional stability were improved. But increase in board density had no significant effect on IB. The results of contour plots showed that manufacturing boards with density of 600-650 Kg/m3and 6% UF resin, all of mechanical properties were maintained in standard specified limits related to those boards and using adequate amount of water resistant materials will Cause improving of thickness swelling after 24 h immersion